A review of 1973 - 1982 tuna fishing activities within nigeria's eez and the options for nigeria - Ajayi, T.O. (Lagos, Nigeria Nigeria Institute for Oceanography & Marine Research, 1984)
This work investigates the availability and abundance of fisheries resources in the EEZ as an indispensable pre-requisite to commercial exploitation
Technical paper No. 16
Includes bibliographical references
osc 04/03/2019
Loans
Keywords: Fisheries; Nigeria